Acute thrombocytopenia and fibrinogen reduction occurring after nintedanib treatment for immune checkpoint inhibitor-related pneumonia: a case report - Zheng, Jian; Zhou, Nan; Pang, Dexiang (Frontiers in Oncology, 2025)
BackgroundNintedanib, a small molecule multi-target tyrosine kinase inhibitor, can block the fibrosis process and slow disease progression. Acute thrombocytopenia and fibrinogen reduction caused by nintedanib is a rare clinical event, with few studies reported.Case presentationWe report the case of an 89-year-old male diagnosed with advanced renal cell carcinoma who developed immune-related interstitial lung disease after treatment with sintilimab injection combined with axitinib. After prescribed nintedanib treatment, the patient’s platelet count decreased from 241×10 μ g/L to 49×10 μ g/L and fibrinogen decreased from 5.61 g/L to 0.76 g/L. Based on the patient’s medical history, laboratory test results, and examination results, the diagnosis was made that it was nintedanib-induced reduction in platelet and fibrinogen levels. After discontinuation of nintedanib, the patient’s platelets and fibrinogen returned to normal, and no further reduction in platelets and fibrinogen was observed during the follow-up period. This case report suggests to physicians that if there is an unexplained decrease in platelet and fibrinogen levels during nintedanib treatment, nintedanib-induced factors should be considered.ConclusionThrombocytopenia and fibrinogens abnormal are rare but serious adverse effect of nintedanib. This case highlights the importance of early recognition and monitoring of platelet counts and coagulation function in patients receiving nintedanib. Suspect drug discontinuation and active supportive care are essential. Further research is needed to elucidate the underlying mechanisms and then make corresponding treatment recommendations.